2021
DOI: 10.1093/brain/awab160
|View full text |Cite
|
Sign up to set email alerts
|

Sex modifies APOE ε4 dose effect on brain tau deposition in cognitively impaired individuals

Abstract: Recent studies in cognitively unimpaired elderly individuals suggest that the APOE ε4 allele exerts a dosage-dependent effect on brain tau deposition. The aim of this study was to investigate sex differences in APOE ε4 gene dosage effects on brain tau deposition in cognitively impaired individuals using quantitative 18F-flortaucipir PET. Preprocessed 18F-flortaucipir tau PET images, T1-weighted structural MRI images, demographic information, global cortical amyloid-β burden measured by 18F-florbetapir PET, CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…In the study, we found more tau deposition in women than men among those who entered the AD disease spectrum and were tau-positive. Previous studies have shown that women have a greater tau burden than men, which is consistent with our findings (Yan et al 2021). In addition, based on ROI analysis, we also found inconsistent regions of interest in the ADNI cohort and the Huashan cohort in which sex caused differences in tau deposition.…”
Section: Discussionsupporting
confidence: 93%
“…In the study, we found more tau deposition in women than men among those who entered the AD disease spectrum and were tau-positive. Previous studies have shown that women have a greater tau burden than men, which is consistent with our findings (Yan et al 2021). In addition, based on ROI analysis, we also found inconsistent regions of interest in the ADNI cohort and the Huashan cohort in which sex caused differences in tau deposition.…”
Section: Discussionsupporting
confidence: 93%
“…There were several limitations in the present study. First, the APOE ε4 allele is termed as the genetic risk factor of AD, which is also exerts a dosage-dependent effect on the risk of AD [49]. Nevertheless, the APOE ε4/ε4 homozygotes only take nearly 10% of AD affected individuals [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…SUVR images were calculated relative to the cerebellum GM (SUVR Cereb_GM ), centrum semiovale (SUVR CS ), and pons (SUVR Pons ) reference tissues. The ROI SUVR values were calculated by applying ROIs on the SUVR images in the standard MNI space for minimizing variance related to the variability of ROI volume and shape in native space (Gottesman et al, 2017; Liu et al, 2019; Paranjpe et al, 2019; Tudorascu et al, 2018; Yan et al, 2021). A total of 18 ROIs including three reference tissues (cerebellum GM, centrum semiovale, and pons) and an additional 15 ROIs including the orbital frontal, prefrontal, superior frontal, medial temporal, inferior temporal, lateral temporal, parietal, posterior precuneus, anterior cingulate, posterior cingulate, occipital, entorhinal cortex, amygdala, hippocampus, and parahippocampal gyrus regions were manually delineated on the MRI template using the PMOD software program (PMOD 4.002, PMOD Technologies Ltd., Zürich, Switzerland) in standard MNI space.…”
Section: Methodsmentioning
confidence: 99%
“…The PET and MRI data were further processed by partial volume correction (PVC) and spatial normalization, both using Statistical Parametric Mapping (SPM12, Wellcome Department of Imaging Neuroscience, Institute of Neurology, London, UK) in the MATLAB R2020b (The MathWorks Inc., Natick, MA) environment, as reported in our earlier studies (Paranjpe et al, 2019;Yan et al, 2020Yan et al, , 2021. PVC was performed to minimize the possibility of underestimation in PET images, especially for small brain regions such as amygdala and striatum.…”
Section: Pet Data Acquisition and Image Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation